PENTINGNYA MANAJEMEN STRATEGI DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Basri, Hasan (Hijri, 2024)
The purpose of this review is to determine the significance of strategic management in raising educational standards. The review approach employed is literature, which involves gathering diverse supporting article references from worldwide and national publications. The study's findings, presented as papers, demonstrate a considerable rise in educational quality in well-managed schools. Schools that are not supported by a good management process can develop an irregular organizational rhythm, resulting in a failure to meet instructional goals. Improving educational quality will undoubtedly benefit school graduates. Strategic management allows for the expansion of future potential while also minimizing realized hazards. Strategic management is only possible if all parties directly involved in the school, such as school administrators, parents of students, lecturers and staff, are involved